Delayed Retropubic Urethroplasty of Completely Transected Urethra Associated With Pelvic Fracture in Girls - Hosseini, Jalil; Tavakkoli Tabassi, Kamyar; Razi, Abdollah (Urology Journal, 2009)
Introduction: The objective of the present study was to evaluate the results and the complications of delayed retropubic urethroplasty of completely transected urethra associated with pelvic fracture in girls.Materials and Methods: From 2002 to 2008, a total of 7 girls with complete urethral disruption after pelvic fracture were referred to our center and all of them underwent delayed retropubic urethroplasty with end-to-end anastomosis of the urethra.Results: Seven female patients with a median age of 6 years old underwent delayed end-to-end anastomosis. The median time to surgery was 6 months from the trauma. Voiding was normal after catheter removal in all of the patients. The median follow-up was 36 months. Three patients had mild stress urinary incontinence after catheter removal.Conclusion: There are some different strategies for management of complete urethral avulsion in females who have sustained pelvic fracture, including early realignment, bladder flaps, and end-to-end anastomosis. The strategy of delayed end-to-end anastomosis urethroplasty with retropubic approach is sound and produces acceptable results. The use of flexible cystoscope and omental flap is effective in achieving continence after urethroplasty in such cases.